2019
DOI: 10.1139/as-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of local Indigenous peoples in Arctic research — expectations, needs and challenges perceived by early career researchers

Abstract: Rapid changes in the natural and social environments of the Arctic region have led to increased scientific presence across the Arctic. Simultaneously, the importance of involving local Indigenous peoples in research activities is increasingly recognized for several reasons, including knowledge sharing and sustainable development. This study explores Arctic early career researchers’ (ECRs) perceptions on involving local Indigenous peoples in their research. The results, based on 108 online survey respondents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Fewer participants stated that they had previous experience working in northern research in 2017 compared to 2016 (33% had worked in northern research in 2017 vs. 53% in 2016). In a recent study, female ECRs rated their knowledge of Indigenous peoples more highly and found more benefits in involving Indigenous peoples in their research than their male counterparts (Sjöberg et al 2019). These trends may have contributed to the predominance of female natural scientists at our workshops.…”
Section: The Intercultural Indigenous Workhopsmentioning
confidence: 76%
See 1 more Smart Citation
“…Fewer participants stated that they had previous experience working in northern research in 2017 compared to 2016 (33% had worked in northern research in 2017 vs. 53% in 2016). In a recent study, female ECRs rated their knowledge of Indigenous peoples more highly and found more benefits in involving Indigenous peoples in their research than their male counterparts (Sjöberg et al 2019). These trends may have contributed to the predominance of female natural scientists at our workshops.…”
Section: The Intercultural Indigenous Workhopsmentioning
confidence: 76%
“…In a 2014 survey of Arctic ECRs from 22 countries, the majority of respondents reported wanting to involve more Indigenous peoples in their research, yet only half felt that they had the basic knowledge to do so. In the same survey, natural scientists rated their knowledge on conducting research with northern Indigenous communities much lower than social scientists (Sjöberg et al 2019). Opportunities do currently exist for Canadian researchers (including ECRs) who want to develop skills for working with Indigenous communities, including massive online courses and courses on research ethics, such as the Carleton University Institute on the Ethics of Research with Indigenous peoples.…”
Section: Introductionmentioning
confidence: 99%
“…Early-career researchers-including graduate students, post-doctoral fellows, and early-career faculty-in the natural sciences typically feel less equipped to conduct research with northern communities than their colleagues in the social sciences (Sjöberg et al 2019), and we were no exception. To improve our research practice, we relied on mentorship (as described earlier) and on Indigenous recommendations (Asselin and Basile 2012; NCAI 2012; Smith 2012; INQ 2017; ITK 2018).…”
Section: Part II Lessons Learned During Outreach Effortsmentioning
confidence: 98%
“…One shortcoming we have identified is that we did not engage stakeholders and Arctic communities directly in the development of research questions related to the ASIAQ goals—rather focusing on outreach—which likely would have made our research more participatory and more meaningful for solving real‐world issues (English et al., 2018). Indigenous voices—and even non‐Indigenous northern voices—are often lost in the conversation about the Arctic once the interests of the Arctic nations are involved (Nilsson & Christensen, 2019), a problem a growing number of Arctic Early Career Researchers is aware of (Sjöberg et al., 2018). Involving stakeholders and communities ensures that solutions to what constitutes a real‐world issue in the Arctic come from the interest of Arctic peoples.…”
Section: Challenge‐driven Strategies For Successful Convergent International Arctic Researchmentioning
confidence: 99%